2014
DOI: 10.1007/s00128-014-1287-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chemical Contaminants on Growth, Age-Structure, and Reproduction of Mytilus edulis Complex from Puget Sound, Washington

Abstract: Bivalves are used as sentinel species to detect chemical contaminants in the marine environment, but biological effects on indigenous populations that result from chemical exposure are largely unknown. We assessed age-weight, length-weight relationships, age structure, and reproductive status (i.e. fecundity, egg size) of the blue mussel Mytilus edulis complex from six sites in central Puget Sound, Washington, and one site in the relatively pristine area of northern Puget Sound. Results of this study suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Pollution may influence the molluscan macrobenthos in a variety of ways. In addition to causing the local extirpation of taxa within the lagoon [45,81], pollution-induced stress is hypothesized to suppress molluscan growth rates [82,83]. Marshal et al [30] found that gastropod Planaxis sulcatus and Echinolittorina nodosus have more globular shells and smaller apertures in polluted water.…”
Section: Pollution-induced Evolutionmentioning
confidence: 99%
“…Pollution may influence the molluscan macrobenthos in a variety of ways. In addition to causing the local extirpation of taxa within the lagoon [45,81], pollution-induced stress is hypothesized to suppress molluscan growth rates [82,83]. Marshal et al [30] found that gastropod Planaxis sulcatus and Echinolittorina nodosus have more globular shells and smaller apertures in polluted water.…”
Section: Pollution-induced Evolutionmentioning
confidence: 99%